A Juridical Analysis of Legal Protection for Healthcare Workers in COVID-19 Patient Services - W.Sihombing; X.Rambe (International Medical Journal Corp. Ltd, 2025)
Introduction: The COVID-19 pandemic placed unprecedented pressure on global healthcare systems, thrusting healthcare workers into high-risk environments with limited initial protocols. In Indonesia, medical professionals faced severe risks of infection, extreme physical exhaustion, and heightened vulnerabilities to civil, criminal, or administrative malpractice claims due to emergency triage conditions. This study examines the structural adequacy of the existing Indonesian legal framework in guaranteeing comprehensive safety and legal immunity for healthcare workers operating under crisis conditions. Methods: This study utilizes a qualitative juridical-normative legal research method, examining primary, secondary, and tertiary legal sources, including the Indonesian Health Law, disaster management statutes, and emergency ministerial decrees. Results: The findings reveal that while statutory provisions theoretically offer right-to-safety protections, operational ambiguities during health emergencies create a significant enforcement gap, leaving practitioners vulnerable to legal disputes and institutional neglect regarding occupational hazards. Discussion: The discussion integrates extensive literature on healthcare jurisprudence, analyzing the conceptual conflicts between standard clinical malpractice criteria and emergency triage exceptions, while evaluating the limits of current administrative indemnification policies. It emphasizes that a lack of synchronized regulations between central labor standards and local hospital protocols weakens the statutory immunity intended for frontline professionals. Conclusions: This study concludes that the legislative framework requires targeted amendments to establish explicit, automatic legal immunity and standardized occupational hazard insurance during declared national health emergencies.